Η ψυχοθεραπεία ως σύστημα και η αναγκαιότητα ενός "ανοίγματος": Παραδείγματα της συστημικής οπτικής στη γνωσιακή-συμπεριφοριστική ψυχοθεραπεία - Α Καλαντζή-Αζίζι; Γαλανάκη, Ε. (Psychology: the Journal of the Hellenic Psychological Society, 2001)
This article is based on the assumption that psychotherapy should operate as an open system in order to improve its effectiveness. This assumption originates from cybernetics and systems theory. The degree to which the "openings" in psychotherapy enhance its effectiveness must be put under systematic empirical investigation. The aim of this article is to discuss several examples of "openings" that reflect the systemic perspective of the cognitive-behavioral methods, as well as the postmodern approach to psychotherapy, in which the cognitive and the systemic aspects are interwoven. These "openings" are evident in the cognitive behavioral family therapy (three models are presented), as well as in the management of problematic situations in the school and in the community (consultation). Moreover, we elaborate on the systemic "openings" with regard to some central concepts of both the systemic and cognitive-behavioral psychotherapy, such as symptom, reinforcement, reframing, circular causality, and resistance.